Estratégias de coping empregadas por enfermeiros hospitalares no contexto da pandemia de Covid-19 - Sousa, Rosângela Aparecida de (2021)
Occupational stress is one of the negative factors present in nursing work, especially in the hospital context, a risk that is aggravated by the covid-19 pandemic. Organizational strategies are essential to reduce stress at work, however individual coping strategies can also contribute to minimizing the impact of stress on workers' lives. This study aimed to understand hospital nurses' coping strategies to cope with occupational stress in the context of the Covid-19 pandemic. This is a qualitative, descriptive, and exploratory study, which was developed in a university hospital located in the inland of the state of São Paulo. The target audience was nurses who have been working within the research field for at least six months. Data were collected through individual virtual interviews, based on a previously defined script of semi-structured questions, and were analyzed according to thematic content analysis. The project was approved by the study setting and the Ethics Committee for Research with Human Beings at UFSCar; all ethical precepts were observed. Through the results of this research, three thematic categories emerged: Suffering at work, Pleasure at work and Coping strategies, the latter being subdivided into three subcategories: Problem-focused coping strategies, Emotion-focused coping strategies, and Coping strategies focused on the problem. meaning. Owing to the results, it was possible to understand the elements that cause suffering in nursing workers and also identify that, even in spite of the Covid-19 pandemic and in the midst of chaos, nursing workers sensed pleasure at work. Faced with stressful situations, is necessary to develop skills to deal with stress. Concerning the coping strategies, the participants in this study evince that they make use of different procedures that are essential in managing occupational stress. In general, actions such as consciously managing coping strategies, social support, self-control, distraction activities, escape-avoidance and reconditioning of positive emotions were contemplated. These are procedures that can contribute to coping with stress at work in a hospital environment, by means of direct action on the problem, reduction of unpleasant effects and emotions and/or positive reinterpretation of the stressor effect. It is concluded that the hospital environment is a workplace that generates suffering in nurses due to its peculiar characteristics and the work overload to which these workers are exposed, and it can also generate pleasure, due to the professional recognition of workers and rehabilitation of patients. Regarding coping, as a way of coping with occupational stress, nurses employed strategies that helped to minimize the impacts caused by work stress. However, as much as nursing workers handle coping measures, organizational strategies are essential to maintain a healthy and safe workplace and reduce occupational stress.